Increased Monocyte Count is Related to the Development of Atrial Fibrillation in Subjects with Heart Failure - Recep Kurt; Anıl Şahin (Medical Laboratory Technology Journal, 2020)
Determining subjects with heart failure (HF), who have a high risk of developing atrial fibrillation (AF), is crucial since it is related to an increase in morbidity and mortality. The importance of an increase in inflammatory response cannot be ignored in developing AF in subjects with HF. This study’s goal was to evaluate the relationship between the development of AF and monocyte count, the main components of the inflammatory response, in subjects with HF. Medical data of 158 subjects in total with sinus rhythm, admitted to the emergency department and hospitalized with systolic HF between January 2009 and February 2014, were analyzed prospectively. All the subjects followed up in terms of the development of AF. The subjects separated into two groups according to their rhythm at the end of the follow-up period. Group 1 included subjects who maintained sinus rhythm, while Group 2 included subjects with AF. Echocardiographic findings and laboratory data were collected. No statistically significant difference was determined between the groups concerning age, sex (p=0.056), hypertension, diabetes mellitus, and smoking status. The two groups differed significantly regarding the presence of moderate-to-severe mitral regurgitation (MR) [32 (28%) vs. 22 (51%), p=0.010] and monocyte count [560 (20-3100) vs. 800 (380-1510) μL, p